Endoscopic Submucosal Dissection of Gastric Superficial Lesions: Predictors for Time of Procedure in a Portuguese Center - Ribeiro-Mourão,Francisco (2015)
Background: Endoscopic submucosal dissection (ESD), an endoscopic technique used for treatment of gastric superficial lesions, has been gaining importance on western countries. Procedural times have an impact on various outcomes. Aim: To define which factors from patients, lesions and procedure can predict longer procedural times. Methods: In a cohort of 127 lesions resected by ESD with IT-knife, after using needle-knife for submucosal layer access, by experienced gastroenterologists, characteristics from the patient (age, gender, presence of co-morbidities, usage and suspension of anti-platelet drugs and general physical condition), lesion (size, histopathological diagnosis at biopsy, location, macroscopic type and submucosal invasion) and procedure (adverse events) were retrospectively analyzed for its impact on time of procedure. Univariate and multivariate analysis were performed. Results: Lesions larger than 20mm (p < 0.001), on the upper third of the stomach (p = 0.035) and with an ASA score of 3 (p = 0.031) were considered influential factors for a longer procedure time and specifically for a time of procedure longer than 90 min. Existence of intra-procedure adverse events was also a predictor for a procedure time >90 min. Lesions size >20mm and location in the upper third were independently associated with a procedure time longer than 90 min (OR 4.91 (95%CI 2.29-10.50) and OR 18.26 (95%CI 2.02-164.78), respectively). Conclusion: The time of procedure of ESD for gastric superficial lesions is influenced by size of lesion (>20mm) and location (upper third of stomach), which predict a time longer than 90 min. This can be useful for better management of workflow, operation, training of teams and anesthesic procedures.